The Relations Among Environmental Performance, Profitability, Firm Size, Firm Value, And Environmental Disclosure: A Case Study of Basic Material Industry - Merlin Berlian; Eka Siskawati; Rasyidah Mustika; Barykin Sergey E.; Catapan Anderson (Publication Division of International Ecsis Association, 2023)
Environmental Disclosure is a information related to the environment, and is presented in financial statements. Financial Accounting Standards do not yet mandate corporate responsibility for environmental disclosures. This study aims to examine the factors that determine environmental disclosure in Indonesia. This research uses quantitative research methods, using secondary data of annual reports and sustainability reports from companies listed on the Indonesia Stock Exchange, especially companies engaged in the Basic Material sector. The data collection of this study used purposive sampling method with several criteria. The test tool used in multiple regression analysis is the Eviews program version 10. Environmental Disclosure uses GRI (Global Reporting Initiatives) standard indicators. Environmental Performance uses the performance ratings in PROPER. While profitability uses ROE (Return on Equity) indicators. Firm Size uses the Asset Growth indicator, and Firm Value uses the Tobin'sq indicator. The results of this study partially show that the firm size variable has an influence on the environmental disclosure variable. Environmental disclosure is not influenced by measures of environmental performance, profitability, or business value. But simultaneously all independent variables, namely environmental performance, profitability, firm size, and firm value affect environmental disclosure.